Retrograde transcatheter device closure of a complex paravalvular leak after bioprosthetic pulmonary valve replacement in a pediatric patient. Issue 7 (30th October 2015) - Chikkabyrappa, Sathish; Mosca, Ralph S.; McElhinney, Doff B.
Abstract : We report a case of retrograde transcatheter device closure of a complex paravalvular leak (PVL) after bioprosthetic pulmonary valve replacement (PVR) in a 13‐year‐old patient with congenital pulmonary valve stenosis. There are prior reports of pulmonary PVL closure after PVR in adults (Seery and Slack, Congenit Heart Dis 2014;9:E19–F22), but indications for and technical considerations in PVL closure after bioprosthetic PVR, particularly in children, are not well defined. © 2015 Wiley Periodicals, Inc.